Adaptation of Accounting Practices in The Era of Globalization: Cultural Comparison Between Indonesia And Malaysia (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to analyze the adaptation of accounting practices in Indonesia and Malaysia within the context of globalization, focusing on the cultural differences that influence the implementation of accounting standards. In the era of globalization, companies in both countries face challenges in enhancing transparency and accountability in their financial reports. The research method employed is qualitative analysis, gathering data from relevant literature, interviews with accounting professionals, and case studies of companies in both countries. The findings of the study reveal that, while Indonesia and Malaysia are working to adopt International Financial Reporting Standards (IFRS), there are significant differences in how the two countries apply accounting practices. In Indonesia, accounting practices are still influenced by local cultural values and a more flexible legal system, while Malaysia demonstrates a higher and more consistent level of IFRS adoption. These findings emphasize the importance of considering cultural and legal contexts in adapting accounting practices. This research makes a significant contribution to stakeholders, including companies and regulators, in understanding the challenges and opportunities in improving accounting practices in the era of globalization. Additionally, it identifies the need for better training and education for accounting professionals in both countries. Therefore, this study is expected to serve as a reference for future research on the adaptation of accounting practices in developing countries.